1985
DOI: 10.1002/ajpa.1330660411
|View full text |Cite
|
Sign up to set email alerts
|

Cranial variation in the terminal Late Archaic of Ohio

Abstract: Cranial and mandibular discrete traits and cranial metric traits were collected from 99-125 individuals in eight terminal Late Archaic sites. The analysis of ten metric traits in six samples showed that the samples shared the same generalized variance and that sexual dimorphism in the means of the metric traits was greater than inter-site differences. Since these samples share the same size and shape expression of a complex set of polygenic traits, we hypothesize a historical relationship among these samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…It is well known that the proportionally shortest legs as well as the shortest distal elements of the limbs can be found among living East Asian populations and populations recently derived from them. However, as Table 1 shows, Ohio Valley Native Americans are characterized by relatively long legs and, as has been shown previously (Sciulli et al, 1991;Sciulli, in press), by relatively long distal elements of the limbs (for example, a brachial index of 77.8 and a crural index of 85.0). Thus, use of regressions based on East Asian populations, or other populations of similar proportions, to estimate stature in Ohio Valley Native Americans will significantly overestimate stature (Sciulli et al, 1990).…”
Section: Discussionmentioning
confidence: 78%
“…It is well known that the proportionally shortest legs as well as the shortest distal elements of the limbs can be found among living East Asian populations and populations recently derived from them. However, as Table 1 shows, Ohio Valley Native Americans are characterized by relatively long legs and, as has been shown previously (Sciulli et al, 1991;Sciulli, in press), by relatively long distal elements of the limbs (for example, a brachial index of 77.8 and a crural index of 85.0). Thus, use of regressions based on East Asian populations, or other populations of similar proportions, to estimate stature in Ohio Valley Native Americans will significantly overestimate stature (Sciulli et al, 1990).…”
Section: Discussionmentioning
confidence: 78%
“…What is lacking in Boas' immigrant study, and what has not been demonstrated yet since Boas, is that environmental plasticity plays a more important role than genetic variation. What has been demonstrated is that cranial dimensions are capable of revealing ''genetic'' patterns in human populations over time and space (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Finally, we address the issue of why Boas published such seemingly erroneous conclusions.…”
Section: Discussionmentioning
confidence: 94%
“…Some nonmetric traits have been shown to have significant genetic components to their expression (Cheverud and Buikstra, 1981;Saunders and Popovich, 1978;Self and Leamy, 1978) and to produce patterns of group relationships consistent with other data under certain conditions (Cheverud and Buikstra, 1978;Lane, 1977;Lane and Sublett, 1972;Sciulli and Schneider, 1985). Nevertheless, other studies have produced data questioning their heritability and utility in population analysis (see, e.g., Corruccini, 1974;Richtsmeier and McGrath, 1986;Wijsman and Neves, 1986).…”
Section: Methodsmentioning
confidence: 91%